Adherence to Repeat Screening Completion for Colorectal Cancer Using the Multi-Target Stool DNA Test: Real-World Analysis of Patients from Federally Qualified Health Centers - Mallik Greene; Timo Pew; Jorge Zapatier; Juliana Vanessa Rincón López; Paul Limburg; Martha Duarte (Journal of Primary Care & Community Health)
Introduction/Objectives: This real-world study examined adherence to repeat mt-sDNA among patients from federally qualified health centers (FQHCs) across the US and among different payer types. Methods: Data from Exact Sciences Laboratories, LLC were used for the period between January 1, 2023, and December 31, 2023, for those who had previously completed a mt-sDNA test. Study outcomes included adherence rate to mt-sDNA repeat screening and time to test return. Results: The study sample consisted of 19 536 eligible patients. The mt-sDNA repeat screening adherence rate was 79.7%, and the mean time to return the kit was 21.1 ± 20.8 days. Repeat screening adherence for patients with Medicare was 84.7%, Medicare Advantage was 80%, commercial insurance was 78.2%, managed care organization was 74.6%, and Medicaid was 65.9% ( P  < .001). Compared with patients covered by commercial insurance, those covered by Medicaid had 42% lower odds of adhering to mt-sDNA repeat screening. Patients with 2 or more prior successful tests had a numerically shorter mean time to test return compared to those with only 1 prior successful test. Conclusions: While repeat screening adherence was generally high across patient demographic categories, there were significant differences by type of insurance coverage and number of prior successful mt-sDNA screenings.